SELECTION OF PRIMERS FOR THE RPOB GENE TO THE PATHOGEN MYCOPLASMA MYCOIDES SUBSP. CAPRI (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article describes the results of studies on the selection of specific primersbased on the rpoB gene of the causative agent of contagious goat pleuropneumonia (CBPP). Forthe selection of specific primers, NCBI resources were used: BLAST nucleotide and PRIMERBLAST. Primer synthesis was carried out by chemical preconcentration on a Synthesyzer H-16device (K&A Laborgeraete). As a result of the work carried out, three pairs of primers for the rpoBgene were selected, satisfying in all respects.
Keywords: goat contagious pleuropneumonia, gene, pathogen.